Analysis of Financing Risk Management at Sharia Pawnshops (Study at the Jelutung Branch of Sharia Pawnshops, Jambi City) - D Amri, Ary; Afrilia Setiawan, Andika; Ibnu Syifa, Ibnu Syifa; Indah Ningrum, Prima; Mutiasari, Rika; -, Wahyudi (ILTIZAM Journal of Shariah Economics Research, 2024)
Financial institutions have an important role in the development of contemporary industrial society. One type of financial institution is a Sharia Pegadaian which offers a pawn system in accordance with Islamic law. Sharia pawnshops have financing risks that must be managed well. This research aims to analyze financing risk management at the Jelutung Sharia Pawnshop, Jambi City. This research uses qualitative methods with case studies. Data collection techniques are carried out through interviews, observation and documentation. Data were analyzed using qualitative data analysis techniques. The results of the research show that Pegadaian Syariah Jelutung, Jambi City implements financing risk management consisting of risk identification, risk measurement, risk control and risk monitoring. Pegadaian Syariah Jelutung, Jambi City uses various methods to identify financing risks, such as qualitative and quantitative analysis. Risk measurement is carried out by calculating the value of the collateral and the customer’s ability to pay. Risk control is carried out by implementing various policies, such as regulatory requirements and law enforcement. Risk monitoring is carried out regularly to ensure the effectiveness of risk management. This research contributes to the understanding of financing risk management at Sharia Pawnshops. The results of this research can be used by Pegadaian Syariah to increase the effectiveness of financing risk management.